Rhetorics and Politics of Materials: from Symbolic Efficacy to Hermetic Semiosis - Cervelli , Pierluigi (E|C, 2023)
This article aims to reflect on the political use of materials, on the models of semiosis underlying such strategies, and on the effects they can have from the point of view of belief, starting from Louis Marin thinking about the portrait of the king. Then the article thematizes the theoretical question of the relationship between matter and materials in relation to two theoretical reflections related to belief: that of Eco on hermetic semiosis and that of Fabbri and Marrone on symbolic efficacy. Finally, the article considers italian fascist regime as a case study from the perspective of political strategies of materials uses, which can be traced back to a hermetic semiosis, in order to emphasize the limits of intersemiotic translation when diversity in the matter of expression arises.